The Needs of People in Tambak Lorok Semarang towards Knowledge - Rizki Nurislaminingsih; Edwin Rizal (Journal of Maritime Studies and National Integration, 2019)
This research has an argumentation that people in Tambak Lorok need additional knowledge to facilitate their work as fishermen. This need is also based on the need to find solutions to problems they often face, such as poverty and lack of it due to dropping out of school. A qualitative approach was used in this study to explore what their necessaries are for knowledge and the reasons behind it. The researchers then use a narrative strategy to describe the research findings. The results show that people in Tambak Lorok need knowledge about marine affairs, technology to catch fish, skills about processing marine products, marketing techniques and about the history of their area or their identity as sailors. They need teachers who are willing to provide training as often as possible with a variety of science themes. They also need additional educational facilities such as village libraries and volunteer teachers as a source of independent learning, especially for children.